2008
DOI: 10.1007/s11433-008-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of surface acoustic wave propagation in a plate of functionally graded materials with a layered model

Abstract: In a homogeneous plate, Rayleigh waves will have a symmetric and anti-symmetric mode regarding to the mid-plane with different phase velocities. If plate properties vary along the thickness, or the plate is of functionally graded material (FGM), the symmetry of modes and frequency behavior will be modified, thus producing different features for engineering applications such as amplifying or reducing the velocity and deformation. This kind of effect can also be easily realized by utilizing a layered structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To break the spatial inversion symmetry, a combined structure composed of a symmetric phononic crystal and an asymmetric structure was proposed [13,17,18]. It is known that the waves propagating in a finite thickness structure, called guided waves, have multi modes [19][20][21][22][23][24]. For example, there are three kinds of guided waves in an elastic layer, i.e., symmetric Lamb wave, antisymmetric Lamb wave, and SH wave, which can be transformed to each other by an asymmetric structure [25].…”
Section: Introductionmentioning
confidence: 99%
“…To break the spatial inversion symmetry, a combined structure composed of a symmetric phononic crystal and an asymmetric structure was proposed [13,17,18]. It is known that the waves propagating in a finite thickness structure, called guided waves, have multi modes [19][20][21][22][23][24]. For example, there are three kinds of guided waves in an elastic layer, i.e., symmetric Lamb wave, antisymmetric Lamb wave, and SH wave, which can be transformed to each other by an asymmetric structure [25].…”
Section: Introductionmentioning
confidence: 99%
“…The work done byWang et al [5] threw light on wave propagation through functionally graded materials; this problem is generally difficult to solve analytically, owing to the presence of variable coefficient differential equations as governing equations, except those with exponential variation in the thickness coordinate. Gao et al [6] suggested the technique of solving functionally graded material layer problems by dividing the initial layer into a number of homogeneous fine layers to facilitate the governing equations of each layer as differential equations with constant coefficients. By virtue of stress and displacements as continuities between the two layers, the problem can be elucidated and solved analytically with credible precision.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the application in piezoelectric material, nondestructive testing, shock absorption and isolation, etc, the theories of wave propagation in functionally graded materials have been widely explored. For the variant coefficients in wave equation of functionally graded materials cause much trouble to derive accurate analytical solution, hence, numerical methods must be applied, for example, homogeneous layer model [3], positive series method [4], Legendre polynomial approach [5], WKB method [6], Piano series method [7], finite element method [8], and so on.…”
Section: Introductionmentioning
confidence: 99%